Estrategias en el uso de dos niveles de hidrolizados de pescado como fuente proteica en la alimentación de pollos de engorde y sus efectos sobre parámetros zootécnicos y morfométricos - Cuchipe Yanqui, Ximena Elizabeth (2021)
During 42 days, the effect of fish hydrolysate supplementation as animal protein was evaluated at two levels of inclusion to enhance productive yields and the incidence of economic indicators in broilers, in the diet fed to 132 male Broiler chickens of the Cobb 500 line of one day old with an average weight of 0.05 kg, using a random distribution of 11 chickens per box having a total of 12 floor boxes in a warehouse of the Technical University of Cotopaxi. From day one until the end of the experimental period the established diets were fed: Initial diet 1 (1 to 8 days of age), initial diet 2 (9 to 18 days of age), growth diet (19 to 28 days of age) and fattening diet (29 to 42 days of age), resulting in three treatments with four replicates each, identified as: T0; Control treatment; T1: 1% fish hydrolyzate; T2: 2% fish hydrolyzate. The vaccination and biosecurity protocol required for each animal was complied with. Weights and daily feed consumption were recorded weekly for subsequent analysis. In the results analysis stage, different productive parameters were calculated to evaluate the response of the chickens to the consumption of fish hydrolysate, thus demonstrating the feed efficiency and the validity of the diet in the productive process. Through a laboratory analysis, the quality of the broiler carcasses for each treatment was determined, thus verifying which of these is viable. The highest weight is (2.76 kg) in T2, with respect to feed consumption, the maximum value was in treatment T0 and the minimum value was in treatment T2. T2 had a positive effect on the growth of the broilers, being the one that presented the best performance, obtaining good results in the zootechnical and morphometric parameters of the animal.